A Review and Critique of Christianity and Democracy - Mokhtar Nouri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The role and position of religion in human political and social life is an issue that must be analyzed for its importance. To address this issue, the present paper looks at one of the most important works in this field, the book The Christianity and Democracy by Jacques Maritain of the French neotomist philosopher. In this work, Maritain has defended democracy by referring to Christianity. Of course, this type of defense is not free of criticism, and Maritain’s work also tragically looks at contemporary democracies. It is clear that the relationship between “religion and democracy” is not limited to Jacques Maritan’s thought, and many thinkers in various intellectual paradigms have addressed this issue. It is also not just about Christianity, and it is one of the most significant topics in the Muslim world. The author has attempted to discuss Jacques Maritain’s theoretical model of the relationship of Christianity and democracy from a political, philosophical, and theological perspective.